The tadpole of the hylodid frog Hylodes charadranaetes Heyer and Cocroft, 1986 - Costa, Paulo Nogueira; Siqueira, Carla Costa; Vrcibradic, Davor; Weber, Luiz Norberto; Rocha, Carlos Frederico D. (Zootaxa, 2010)
The genus Hylodes Fitzinger, 1826 is restricted to eastern Brazil, occurring from the states of Espírito Santo to Rio Grande do Sul (Lingnau et al. 2008, Frost 2010). Except for Hylodes otavioi, which inhabits riparian forests in rocky fields (“campos rupestres”) habitats within the Cerrado domain in Minas Gerais State (Sazima & Bokermann 1982), all other species in the genus are endemic to the Atlantic Rainforest domain (Lingnau et al. 2008). The genus currently comprises 24 species (Frost 2010) of small to medium-sized diurnal frogs that live associated to lotic streams in forests (e.g. Lingnau et al. 2008; Silva & Benmaman 2008). Heyer (1982) proposed four species groups for Hylodes, which are still recognized today (but see Haddad et al. 1996; Canedo & Pombal 2007): the glaber (formerly pulcher), lateristrigatus, mertensi, and nasus species groups. The Hylodes lateristrigatus species group is the most specious, being currently composed by 18 species: H. amnicola Pombal, Feio, and Haddad, 2002, H. babax Heyer, 1982, H. charadranaetes Heyer and Cocroft, 1986, H. fredi Canedo and Pombal, 2007, H. heyeri Haddad, Pombal, and Bastos, 1996, H. lateristrigatus (Baumann, 1912), H. magalhaesi (Bokermann, 1964), H. meridionalis (Mertens, 1927), H. ornatus (Bokermann, 1967), H. otavioi Sazima and Bokermann, 1983, H. perere Silva & Benmaman, 2008, H. perplicatus (Miranda-Ribeiro, 1926), H. pipilans Canedo and Pombal, 2007, H. phyllodes Heyer and Cocroft, 1986, H. regius Gouvêa, 1979, H. sazimai Haddad and Pombal, 1995, H. uai Nascimento, Pombal, and Haddad, 2001, and H. vanzolinii Heyer, 1982 (Silva & Benmaman 2008; Frost 2010).